Underwater sensor network for monitoring applications - Kuan, Yee Chiang (Universiti Malaysia Sarawak (UNIMAS), 2009)
The oceans alone cover almost three quarters (71%) of our planet and along with rivers and lakes are critical to our well-being. They must be continuously observed to detect climate changes or pollution of the environment which effects human and animal habitat, especially in this 21st century which global warming is the main issue. Recently, sensor networks have appeared as an important technique for many applications, including monitoring, measurement, surveillance and control. The idea of applying sensor networks for underwater monitoring has become more interests. In this thesis, the development of an underwater sensor that able to perform monitoring applications is described. The systems and technologies of underwater sensor network has been carried out and investigated for a better understanding. Few possible solutions of designing the system are discussed and a more suitable solution for real time monitoring is proposed. By the development of the proposed underwater sensor network monitoring system, any changing on the water quality should be able to monitor instantly by the end user, which consists of related research group or organization and society.